Vadim Abdrashitov's workshop: a place for discipline, a place for art. (4th May 2019) - Nemchenko, Lilya
ABSTRACT: Part of a special issue devoted to the centenary of the Film Institute VGIK, this article explores the concept of the 'workshop' with Vadim Abdrashitov as a case study. The films by Abdrashitov's students from different cohorts taught at VGIK are analysed in order to tease out the essential features of his teaching: the emphasis on the here and now, the engagement with human values, and the conflict between the reality of life and absolute truth. The concept of the 'workshop' as a structural unit for teaching young filmmakers at VGIK is defined, where the bond lies not between the themes, but in human values promulgated in student films by Igor' Khomskii, Evgeniia Iatskina, Nastasia Simbirtseva, Gala Sukhanova and Sonia Chernysheva, as well as more recently by Anna Dezhurko, and by an older cohort including Aleksei Mizgirev. Their features are compared with Abdrashitov's own films.